Achieving temporary divertor plasma detachment with MARFE events by pellet injection in the EAST superconducting tokamak. (23rd November 2016) - Deng (邓国忠), Guozhong; Wang (王亮), Liang; Liu (刘晓菊), Xiaoju; Duan (段艳敏), Yanmin; Hu (胡建生), Jiansheng; Li (李长征), Changzheng; Zhang (张凌), Ling; Liu (刘少承), Shaocheng; Wang (汪惠乾), Huiqian; Chen (陈良), Liang; Xu (许吉禅), Jichan; Feng (冯威), Wei; et al.
Abstract: A new pellet injection system has been equipped on the experimental advanced superconducting tokamak (EAST) in the 2012 campaign, with a pellet size of ϕ 2 mm × 2 mm, a frequency of 1 Hz–10 Hz and velocity of 150 m s −1 –300 m s −1 . The deuterium pellet is well-known for plasma fuelling as well as for  triggering the edge localized mode (ELM). In the 2012 campaign, pellet injection experiments were successfully carried out on EAST. Temporary plasma detachment achieved by deuterium pellets has been observed in a double null (DN) divertor configuration, with multi-pellet injections at a repetition frequency of 2 Hz. The partial detachment of the outer divertors and complete detachment of the inner divertors was achieved after 35 ms of each pellet injection, which have a duration of 30–60 ms with the maximum degree of detachment ( DOD ) reaching 3.5 and 37, respectively. Meanwhile, the multifaceted asymmetric radiation from the edge (MARFE) phenomena was also observed at the high field side (HFS) near both the lower and upper X-points with radiation loss suddenly increased to about 15%–70%, which may be the main cause of divertor plasma detachment. The temporary detachment induced by pellet injection may act as a new way to study divertor detachment behaviors.